What Drives Risky Prescription Opioid Use? Evidence From Migration - Amy Finkelstein; Matthew Gentzkow; Dean Li (The Quarterly Journal of Economics, 2025)
ABSTRACT We develop and estimate a dynamic model of risky prescription opioid use that allows us to unpack the role of person- and place-specific drivers of the opioid epidemic and assess the impact of state opioid policies. Event studies indicate that among adults receiving federal disability insurance from 2006 to 2019, moves to states with higher rates of risky use produce an immediate jump in the probability of risky use, followed by an additional gradual increase for the next several years. Using a potential-outcomes framework, we show how these results map to the person- and place-specific factors in the model. Model estimates imply large effects of place on both the likelihood of transitioning to addiction and the availability of prescription opioids; they also indicate that these place effects change significantly when state laws restricting pain clinics are enacted. A one standard deviation reduction in all place effects would have reduced risky use by about 40% over our study period. One particular source of place effects, pain clinic laws, reduced risky use by 5%, but could have reduced it by 30% if they had been enacted earlier, with much of this magnification operating through the dynamics of addiction.